Knowledge worker training in Malaysia - Zulkifli, Izyani (2010)
An increasing number of countries have shifted, or are shifting, towards the knowledge-based economy. For these countries, including Malaysia, the quality of knowledge workers is extremely important in determining the pace and success of such transition. Thus, training is often carried out to improve the skills of knowledge workers at the workplace. But despite its importance, research on knowledge worker training is extremely limited. This study seeks to partially fill this gap in the literature by investigating three aspects of knowledge worker training in Malaysia. Using an online survey, data is collected from a sample of companies and knowledge workers in MSC Malaysia.